Pengembangan Lembar Kerja Siswa (LKS) untuk Meningkatkan Kemampuan Penalaran dan Literasi Matematis - Handriastuti, Sri Wening; Murtianto, Yanuar Hery; Sutrisno, Sutrisno (Institut Agama Islam Negeri Curup, 2024)
Mathematical reasoning and literacy abilities are abilities every person must have today to keep up with current developments. These two abilities are honed through learning mathematics at school. In learning, appropriate media is needed. This research aims to develop mathematical reasoning and literacy skills through student worksheets. Research and Development research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The data collection technique in this research uses tests. Data analysis techniques use the multivariate normality test, covariance matrix homogeneity test, Hotelling test, and post-Hotelling test. Before use, student worksheets are validated by media experts and material experts. The results were for media experts, and for material experts, so the student worksheet was suitable for use. Student responses regarding using student worksheets in the experimental class showed , which means the student worksheets are practical. The final data analysis (posttest) shows that the average mathematical reasoning and literacy abilities in classes that use student worksheets are better than in classes that do not.